FEVER AS KEY SYMPTOM OF ACUTE RESPIRATORY INFECTIONS AND MODERN METHODS OF THERAPY FOR HIGH TEMPERATURE IN CHILDREN - O.A. Solntseva ("Paediatrician" Publishers LLC, 2010)
Hyperthermia is the key symptom of acute respiratory infections (ARI). An increase in the body temperature is accompanied with phagocytosis activation, increased interferon synthesis, antibody genesis stimulation, lymphocytes activation and differentiation. Nevertheless, significant hyperthermia may result in my unfavourable consequences. It may particularly cause an exacerbation of chronic diseases. Modern therapy for hyperthermia is, therefore, an important aspect of treating children with ARI. The article outlines the modern approach to treating fever in children, identifies key criteria for selecting a medication. It also contains a case study of applying ibuprofen and data from various trials which verify the rationale for applying ibuprofen in children with hyperthermia that developed in conjunction with ARI. Key words: children, acute respiratory infections, hyperthermia, ibuprofen. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(5):80-84)